The inveterate failures of the international community on Somali impasse - Shuriye, Abdi Omar (IDOSI Publications, 2012)
This research evaluates the failures of the international community to solve the long standing political impulse that has generated humanitarian crisis as well as political, social and military instabilities in Somalia and in the horn of Africa. The nucleus objective of the research is to explicate critically the causes of the failures. Prior to this research no definite work has been done on the subject. The research therefore, investigates the methodology and the strategic framework adopted by the international community in reinstating or overcoming the Somali political and humanitarian impasse. The political history of Somalia is long and painful; as the ruthless civil war ruined the nation for the past two and half decades. Once the central government crumpled in 1991 the institutional structures of the nation went into an eminent impasse. The research adopts evaluative method to cover wider range of ideas and assess the subject matter comprehensively.